A cochlear-bone wave can yield a hearing sensation as well as otoacoustic emission - Tchumatchenko, Tatjana; Reichenbach, Tobias (Nature Communications, 2014)
A hearing sensation arises when the elastic basilar membrane inside the cochlea vibrates. The basilar membrane is typically set into motion through airborne sound that displaces the middle ear and induces a pressure difference across the membrane. A second, alternative pathway exists, however: stimulation of the cochlear bone vibrates the basilar membrane as well. This pathway, referred to as bone conduction, is increasingly used in headphones that bypass the ear canal and the middle ear. Furthermore, otoacoustic emissions, sounds generated inside the cochlea and emitted therefrom, may not involve the usual wave on the basilar membrane, suggesting that additional cochlear structures are involved in their propagation. Here we describe a novel propagation mode within the cochlea that emerges through deformation of the cochlear bone. Through a mathematical and computational approach we demonstrate that this propagation mode can explain bone conduction as well as numerous properties of otoacoustic emissions. © 2014 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2021-02-25

A hydrodynamic sensory antenna used by killifish for nocturnal hunting - Schwarz, Jason S.; Reichenbach, Tobias; Hudspeth, A. J. (Journal of Experimental Biology, 2011)
The perception of sensory stimuli by an animal requires several steps, commencing with the capture of stimulus energy by an antenna that, as the interface between the physical world and the nervous system, modifies the stimulus in ways that enhance the animal's perception. The mammalian external ear, for example, collects sound and spectrally alters it to increase sensitivity and improve the detection of directionality. In view of the morphological diversity of the lateral-line system across species and its accessibility to observation and experimental intervention, we sought to investigate the role of antennal structures on the response characteristics of the lateral line. The surface-feeding killifish Aplocheilus lineatus is able to hunt in darkness by detecting surface capillary waves with the lateral-line system atop its head. This cephalic lateral line consists of a stereotyped array of 18 mechanosensitive neuromasts bordered by fleshy ridges. By recording microphonic potentials, we found that each neuromast has a unique receptive field defined by its sensitivity to stimulation of the water's surface. The ridges help determine these receptive fields by altering the flow of water over each neuromast. Modification of the hydrodynamic environment by the addition of a supplemental ridge changes the pattern of water movement, perturbs the receptive fields of adjacent neuromasts and impairs the fish's localization ability. On the basis of electrophysiological, hydrodynamic and behavioral evidence, we propose that the ridges constitute a hydrodynamic antenna for the cephalic lateral line. © 2011. Published by The Company of Biologists Ltd.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Capillary wave; Hair cell; Neuromast

A ratchet mechanism for amplification in low-frequency mammalian hearing - Reichenbach, Tobias; Hudspeth, A. J. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The sensitivity and frequency selectivity of hearing result from tuned amplification by an active process in the mechanoreceptive hair cells. In most vertebrates, the active process stems from the active motility of hair bundles. The mammalian cochlea exhibits an additional form of mechanical activity termed electromotility: its outer hair cells (OHCs) change length upon electrical stimulation. The relative contributions of these two mechanisms to the active process in the mammalian inner ear is the subject of intense current debate. Here,we show that active hair-bundle motility and electromotility can together implement an efficient mechanism for amplification that functions like a ratchet: Sound-evoked forces, acting on the basilar membrane, are transmitted to the hair bundles, whereas electromotility decouples active hair-bundle forces from the basilar membrane. This unidirectional coupling can extend the hearing range well below the resonant frequency of the basilar membrane. It thereby provides a concept for low-frequency hearing that accounts for a variety of unexplained experimental observations from the cochlear apex, including the shape and phase behavior of apical tuning curves, their lack of significant nonlinearities, and the shape changes of threshold tuning curves of auditory-nerve fibers along the cochlea. The ratchet mechanism constitutes a general design principle for implementing mechanical amplification in engineering applications.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Auditory system; Cochlea; Hair cell

Attentional modulation of the cortical contribution to the frequency-following response evoked by continuous speech - Schüller, Alina; Schilling, Achim; Krauß, Patrick; Rampp, Stefan; Reichenbach, Tobias (The Journal of Neuroscience, 2023)
Selective attention to one of several competing speakers is required for comprehending a target speaker amongst other voices and for successful communication with them. It moreover has been found to involve the neural tracking of low-frequency speech rhythms in the auditory cortex. Effects of selective attention have also been found in subcortical neural activities, in particular regarding the high-frequency neural response at the fundamental frequency of speech, the speech-FFR. Recent investigations have, however, shown that the speech-FFR contains cortical contributions as well. It remains unclear whether these are also modulated by selective attention. Here we employed magnetoencephalography (MEG) to assess the attentional modulation of the cortical contributions to the speech-FFR. We presented both male and female participants with two competing speech signals and analyzed the cortical responses during attentional switching between the two speakers. Our findings revealed robust attentional modulation of the cortical contribution to the speech-FFR: the neural responses were higher when the speaker was attended than when they were ignored. We also found that, regardless of attention, a voice with a lower fundamental frequency elicited a larger cortical contribution to the speech-FFR than a voice with a higher fundamental frequency. Our results show that the attentional modulation of the speech-FFR does not only occur subcortically but extends to the auditory cortex as well.
CRIS-Team Scopus Importer:2023-11-17

Audiotactile Stimulation Can Improve Syllable Discrimination through Multisensory Integration in the Theta Frequency Band - Guilleminot, Pierre; Graef, Cosima; Butters, Emilia; Reichenbach, Tobias (Journal of Cognitive Neuroscience, 2023)
Syllables are an essential building block of speech. We recently showed that tactile stimuli linked to the perceptual centers of syllables in continuous speech can improve speech comprehension. The rate of syllables lies in the theta frequency range, between 4 and 8 Hz, and the behavioral effect appears linked to multisensory integration in this frequency band. Because this neural activity may be oscillatory, we hypothesized that a behavioral effect may also occur not only while but also after this activity has been evoked or entrained through vibrotactile pulses. Here, we show that audiotactile integration regarding the perception of single syllables, both on the neural and on the behavioral level, is consistent with this hypothesis. We first stimulated participants with a series of vibrotactile pulses and then presented them with a syllable in background noise. We show that, at a delay of 200 msec after the last vibrotactile pulse, audiotactile integration still occurred in the theta band and syllable discrimination was enhanced. Moreover, the dependence of both the neural multisensory integration as well as of the behavioral discrimination on the delay of the audio signal with respect to the last tactile pulse was consistent with a damped oscillation. In addition, the multisensory gain is correlated with the syllable discrimination score. Our results therefore evidence the role of the theta band in audiotactile integration and provide evidence that these effects may involve oscillatory activity that still persists after the tactile stimulation.
CRIS-Team Scopus Importer:2023-10-20

AVbook, a high-frame-rate corpus of narrative audiovisual speech for investigating multimodal speech perception - Varano, Enrico; Guilleminot, Pierre; Reichenbach, Tobias (Journal of the Acoustical Society of America, 2023)
Seeing a speaker's face can help substantially with understanding their speech, particularly in challenging listening conditions. Research into the neurobiological mechanisms behind audiovisual integration has recently begun to employ continuous natural speech. However, these efforts are impeded by a lack of high-quality audiovisual recordings of a speaker narrating a longer text. Here, we seek to close this gap by developing AVbook, an audiovisual speech corpus designed for cognitive neuroscience studies and audiovisual speech recognition. The corpus consists of 3.6 h of audiovisual recordings of two speakers, one male and one female, each reading 59 passages from a narrative English text. The recordings were acquired at a high frame rate of 119.88 frames/s. The corpus includes phone-level alignment files and a set of multiple-choice questions to test attention to the different passages. We verified the efficacy of these questions in a pilot study. A short written summary is also provided for each recording. To enable audiovisual synchronization when presenting the stimuli, four videos of an electronic clapperboard were recorded with the corpus. The corpus is publicly available to support research into the neurobiology of audiovisual speech processing as well as the development of computer algorithms for audiovisual speech recognition.
CRIS-Team Scopus Importer:2023-06-16

A wave of cochlear bone deformation can underlie bone conduction and otoacoustic emissions - Tchumatchenko, Tatjana; Reichenbach, Tobias (AIP Conference Proceedings, 2015)
A sound signal is transmitted to the cochlea through vibration of the middle ear that induces a pressure difference across the cochlea's elastic basilar membrane. In an alternative pathway for transmission, the basilar membrane can also be deflected by vibration of the cochlear bone, without participation of the middle ear. This second pathway, termed bone conduction, is increasingly used in commercial applications, namely in bone-conduction headphones that deliver sound through vibration of the skull. The mechanism of this transmission, however, remains unclear. Here, we study a cochlear model in which the cochlear bone is deformable. We show that deformation of the cochlear bone, such as resulting from bone stimulation, elicits a wave on the basilar membrane and can hence explain bone conduction. Interestingly, stimulation of the basilar membrane can in turn elicit a wave of deformation of the cochlear bone. We show that this has implications for the propagation of otoacoustic emissions: these can emerge from the cochlea through waves of bone deformation.
CRIS-Team Scopus Importer:2021-02-25

Characterisation of the static offset in the travelling wave in the cochlear basal turn - Ota, Takeru; Nin, Fumiaki; Choi, Samuel; Muramatsu, Shogo; Sawamura, Seishiro; Ogata, Genki; Sato, Mitsuo P.; Doi, Katsumi; Doi, Kentaro; Tsuji, Tetsuro; Kawano, Satoyuki; Reichenbach, Tobias; et al. (Pflügers Archiv: European Journal of Physiology, 2020)
In mammals, audition is triggered by travelling waves that are evoked by acoustic stimuli in the cochlear partition, a structure containing sensory hair cells and a basilar membrane. When the cochlea is stimulated by a pure tone of low frequency, a static offset occurs in the vibration in the apical turn. In the high-frequency region at the cochlear base, multi-tone stimuli induce a quadratic distortion product in the vibrations that suggests the presence of an offset. However, vibrations below 100 Hz, including a static offset, have not been directly measured there. We therefore constructed an interferometer for detecting motion at low frequencies including 0 Hz. We applied the interferometer to record vibrations from the cochlear base of guinea pigs in response to pure tones. When the animals were exposed to sound at an intensity of 70 dB or higher, we recorded a static offset of the sinusoidally vibrating cochlear partition by more than 1 nm towards the scala vestibuli. The offset’s magnitude grew monotonically as the stimuli intensified. When stimulus frequency was varied, the response peaked around the best frequency, the frequency that maximised the vibration amplitude at threshold sound pressure. These characteristics are consistent with those found in the low-frequency region and are therefore likely common across the cochlea. The offset diminished markedly when the somatic motility of mechanosensitive outer hair cells, the force-generating machinery that amplifies the sinusoidal vibrations, was pharmacologically blocked. Therefore, the partition offset appears to be linked to the electromotile contraction of outer hair cells.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Offset; Outer hair cells; Somatic motility; Travelling wave; Vibration

Coexistence in a one-dimensional cyclic dominance process - Winkler, Anton A.; Reichenbach, Tobias; Frey, Erwin (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2010)
Cyclic (rock-paper-scissors-type) population models serve to mimic complex species interactions. Focusing on a paradigmatic three-species model with mutations in one dimension, we observe an interplay between equilibrium and nonequilibrium processes in the stationary state. We exploit these insights to obtain asymptotically exact descriptions of the emerging reactive steady state in the regimes of high and low mutation rates. The results are compared to stochastic lattice simulations. Our methods and findings are potentially relevant for the spatiotemporal evolution of other nonequilibrium stochastic processes. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2021-02-25

Computational modeling of the auditory brainstem response to continuous speech - Saiz-Alia, Marina; Reichenbach, Tobias (Journal of Neural Engineering, 2020)
Objective. The auditory brainstem response can be recorded non-invasively from scalp electrodes and serves as an important clinical measure of hearing function. We have recently shown how the brainstem response at the fundamental frequency of continuous, non-repetitive speech can be measured, and have used this measure to demonstrate that the response is modulated by selective attention. However, different parts of the speech signal as well as several parts of the brainstem contribute to this response. Here we employ a computational model of the brainstem to elucidate the influence of these different factors. Approach. We developed a computational model of the auditory brainstem by combining a model of the middle and inner ear with a model of globular bushy cells in the cochlear nuclei and with a phenomenological model of the inferior colliculus. We then employed the model to investigate the neural response to continuous speech at different stages in the brainstem, following the methodology developed recently by ourselves for detecting the brainstem response to running speech from scalp recordings. We compared the simulations with recordings from healthy volunteers. Main results. We found that the auditory-nerve fibers, the cochlear nuclei and the inferior colliculus all contributed to the speech-evoked brainstem response, although the dominant contribution came from the inferior colliculus. The delay of the response corresponded to that observed in experiments. We further found that a broad range of harmonics of the fundamental frequency, up to about 8 kHz, contributed to the brainstem response. The response declined with increasing fundamental frequency, although the signal-to-noise ratio was largely unaffected. Significance. Our results suggest that the scalp-recorded brainstem response at the fundamental frequency of speech originates predominantly in the inferior colliculus. They further show that the response is shaped by a large number of higher harmonics of the fundamental frequency, reflecting highly nonlinear processing in the auditory periphery and illustrating the complexity of the response.
CRIS-Team Scopus Importer:2021-02-25
Keywords: auditory brainstem response; auditory periphery; computational model; speech

Contribution of active hair-bundle motility to nonlinear amplification in the mammalian cochlea - Nin, Fumiaki; Reichenbach, Tobias; Fisher, Jonathan A. N.; Hudspeth, A. J. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
The cochlea's high sensitivity stems from the active process of outer hair cells, which possess two force-generating mechanisms: active hair-bundle motility elicited by Ca2+ influx and somatic motility mediated by the voltage-sensitive protein prestin. Although interference with prestin has demonstrated a role for somatic motility in the active process, it remains unclear whether hair-bundle motility contributes in vivo. We selectively perturbed the two mechanisms by infusing substances into the endolymph or perilymph of the chinchilla's cochlea and then used scanning laser interferometry to measure vibrations of the basilar membrane. Blocking somatic motility, damaging the tip links of hair bundles, or depolarizing hair cells eliminated amplification. While reducing amplification to a lesser degree, pharmacological perturbation of active hair-bundle motility diminished or eliminated the nonlinear compression underlying the broad dynamic range associated with normal hearing. The results suggest that active hair-bundle motility plays a significant role in the amplification and compressive nonlinearity of the cochlea.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Auditory system; Hopf bifurcation

Cortical Response to the Natural Speech Envelope Correlates with Neuroimaging Evidence of Cognition in Severe Brain Injury - Braiman, Chananel; Fridman, Esteban A.; Conte, Mary M.; Voss, Henning U.; Reichenbach, Chagit S.; Reichenbach, Tobias; Schiff, Nicholas D. (Current Biology, 2018)
Recent studies identify severely brain-injured patients with limited or no behavioral responses who successfully perform functional magnetic resonance imaging (fMRI) or electroencephalogram (EEG) mental imagery tasks [1–5]. Such tasks are cognitively demanding [1]; accordingly, recent studies support that fMRI command following in brain-injured patients associates with preserved cerebral metabolism and preserved sleep-wake EEG [5, 6]. We investigated the use of an EEG response that tracks the natural speech envelope (NSE) of spoken language [7–22] in healthy controls and brain-injured patients (vegetative state to emergence from minimally conscious state). As audition is typically preserved after brain injury, auditory paradigms may be preferred in searching for covert cognitive function [23–25]. NSE measures are obtained by cross-correlating EEG with the NSE. We compared NSE latencies and amplitudes with and without consideration of fMRI assessments. NSE latencies showed significant and progressive delay across diagnostic categories. Patients who could carry out fMRI-based mental imagery tasks showed no statistically significant difference in NSE latencies relative to healthy controls; this subgroup included patients without behavioral command following. The NSE may stratify patients with severe brain injuries and identify those patients demonstrating “cognitive motor dissociation” (CMD) [26] who show only covert evidence of command following utilizing neuroimaging or electrophysiological methods that demand high levels of cognitive function. Thus, the NSE is a passive measure that may provide a useful screening tool to improve detection of covert cognition with fMRI or other methods and improve stratification of patients with disorders of consciousness in research studies.
CRIS-Team Scopus Importer:2021-02-25
Keywords: cognitive motor dissociation; coma; disorders of consciousness; EEG; fMRI; minimally conscious state; speech envelope; speech perception; traumatic brain injury; vegetative state

Cortical tracking of surprisal during continuous speech comprehension - Weissbart, Hugo; Kandylaki, Katerina D.; Reichenbach, Tobias (Journal of Cognitive Neuroscience, 2019)
Speech comprehension requires rapid online processing of a continuous acoustic signal to extract structure and meaning. Previous studies on sentence comprehension have found neural correlates of the predictability of a word given its context, as well as of the precision of such a prediction. However, they have focused on single sentences and on particular words in those sentences. Moreover, they compared neural responses to words with low and high predictability, as well as with low and high precision. However, in speech comprehension, a listener hears many successive words whose predictability and precision vary over a large range. Here, we show that cortical activity in different frequency bands tracks word surprisal in continuous natural speech and that this tracking is modulated by precision. We obtain these results through quantifying surprisal and precision from naturalistic speech using a deep neural network and through relating these speech features to EEG responses of human volunteers acquired during auditory story comprehension. We find significant cortical tracking of surprisal at low frequencies, including the delta band as well as in the higher frequency beta and gamma bands, and observe that the tracking is modulated by the precision. Our results pave the way to further investigate the neurobiology of natural speech comprehension.
CRIS-Team Scopus Importer:2021-02-25

Decoding Envelope and Frequency-Following EEG Responses to Continuous Speech Using Deep Neural Networks - Thornton, Mike; Mandic, Danilo P.; Reichenbach, Tobias (IEEE Open Journal of Signal Processing, 2024)
The electroencephalogram (EEG) offers a non-invasive means by which a listener's auditory system may be monitored during continuous speech perception. Reliable auditory-EEG decoders could facilitate the objective diagnosis of hearing disorders, or find applications in cognitively-steered hearing aids. Previously, we developed decoders for the ICASSP Auditory EEG Signal Processing Grand Challenge (SPGC). These decoders aimed to solve the match-mismatch task: given a short temporal segment of EEG recordings, and two candidate speech segments, the task is to identify which of the two speech segments is temporally aligned, or matched, with the EEG segment. The decoders made use of cortical responses to the speech envelope, as well as speech-related frequency-following responses, to relate the EEG recordings to the speech stimuli. Here we comprehensively document the methods by which the decoders were developed. We extend our previous analysis by exploring the association between speaker characteristics (pitch and sex) and classification accuracy, and provide a full statistical analysis of the final performance of the decoders as evaluated on a heldout portion of the dataset. Finally, the generalisation capabilities of the decoders are characterised, by evaluating them using an entirely different dataset which contains EEG recorded under a variety of speech-listening conditions. The results show that the match-mismatch decoders achieve accurate and robust classification accuracies, and they can even serve as auditory attention decoders without additional training.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Auditory attention decoding; Auditory system; Decoding; Deep learning; EEG signal processing; Electrodes; Electroencephalography; Noise measurement; Recording; Task analysis

Decoding of selective attention to continuous speech from the human auditory brainstem response - Etard, Octave; Kegler, Mikolaj; Braiman, Chananel; Forte, Antonio Elia; Reichenbach, Tobias (NeuroImage, 2019)
Humans are highly skilled at analysing complex acoustic scenes. The segregation of different acoustic streams and the formation of corresponding neural representations is mostly attributed to the auditory cortex. Decoding of selective attention from neuroimaging has therefore focussed on cortical responses to sound. However, the auditory brainstem response to speech is modulated by selective attention as well, as recently shown through measuring the brainstem's response to running speech. Although the response of the auditory brainstem has a smaller magnitude than that of the auditory cortex, it occurs at much higher frequencies and therefore has a higher information rate. Here we develop statistical models for extracting the brainstem response from multi-channel scalp recordings and for analysing the attentional modulation according to the focus of attention. We demonstrate that the attentional modulation of the brainstem response to speech can be employed to decode the attentional focus of a listener from short measurements of 10 s or less in duration. The decoding remains accurate when obtained from three EEG channels only. We further show how out-of-the-box decoding that employs subject-independent models, as well as decoding that is independent of the specific attended speaker is capable of achieving similar accuracy. These results open up new avenues for investigating the neural mechanisms for selective attention in the brainstem and for developing efficient auditory brain-computer interfaces.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Auditory attention decoding; Complex auditory brainstem response; Natural speech

Decoding the neural processing of selective attention to speech - Reichenbach, Tobias (Proceedings of the International Congress on Acoustics, 2019)
Understanding speech in noisy backgrounds requires selective attention to a particular speaker. Humans excel at this challenging task, while current speech recognition technology still struggles when background noise is loud. The neural mechanisms by which we attend selectively to a particular speech signal remain, however, poorly understood, not least due to the complexity of natural speech. Here we describe recent progress obtained through applying machine-learning to neuroimaging data of humans listening to speech in background noise. In particular, we develop statistical models to relate two characteristic features of speech, pitch and amplitude fluctuations, to neural measurements. We find neural correlates of speech processing both at the subcortical level, related to the pitch, as well as at the cortical level, related to amplitude fluctuations. Our findings may be applied in smart hearing aids that automatically adjust speech processing to assist a user, as well as inform future speech-recognition algorithms.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Neural processing; Noise; Speech

Detecting Gamma-Band Responses to the Speech Envelope for the ICASSP 2024 Auditory EEG Decoding Signal Processing Grand Challenge - Thornton, Mike; Auernheimer, Jonas; Jehn, Constantin; Mandic, Danilo; Reichenbach, Tobias (2024 IEEE International Conference on Acoustics, Speech, and Signal Processing Workshops, ICASSPW 2024 - Proceedings, 2024)
The 2024 ICASSP Auditory EEG Signal Processing Grand Challenge concerns the decoding of electroencephalography (EEG) measurements taken from participants who listened to speech material. This work details our solution to the match-mismatch sub-task: given a short temporal segment of EEG recordings and several candidate speech segments, the task is to classify which of the speech segments was time-aligned with the EEG signals. We show that high-frequency gamma-band responses to the speech envelope can be detected with a high accuracy. By jointly assessing gamma-band responses and low-frequency envelope tracking, we develop a match-mismatch decoder which placed first in this task.
CRIS-Team Scopus Importer:2024-09-06
Keywords: deep learning; EEG decoding; speech

Development of New Open-Set Speech Material for Use in Clinical Audiology with Speakers of British English - Keshavarzi, Mahmoud; Salorio-Corbetto, Marina; Reichenbach, Tobias; Marriage, Josephine; Moore, Brian C.J. (Audiology Research, 2024)
Background: The Chear open-set performance test (COPT), which uses a carrier phrase followed by a monosyllabic test word, is intended for clinical assessment of speech recognition, evaluation of hearing-device performance, and the fine-tuning of hearing devices for speakers of British English. This paper assesses practice effects, test–retest reliability, and the variability across lists of the COPT. Method: In experiment 1, 16 normal-hearing participants were tested using an initial version of the COPT, at three speech-to-noise ratios (SNRs). Experiment 2 used revised COPT lists, with items swapped between lists to reduce differences in difficulty across lists. In experiment 3, test–retest repeatability was assessed for stimuli presented in quiet, using 15 participants with sensorineural hearing loss. Results: After administration of a single practice list, no practice effects were evident. The critical difference between scores for two lists was about 2 words (out of 15) or 5 phonemes (out of 50). The mean estimated SNR required for 74% words correct was −0.56 dB, with a standard deviation across lists of 0.16 dB. For the participants with hearing loss tested in quiet, the critical difference between scores for two lists was about 3 words (out of 15) or 6 phonemes (out of 50).
CRIS-Team Scopus Importer:2024-05-03
Keywords: open-set speech material; phoneme analysis; speech test; word analysis

Discrimination of Low-Frequency Tones Employs Temporal Fine Structure - Reichenbach, Tobias; Hudspeth, A. J. (PLoS ONE, 2012)
An auditory neuron can preserve the temporal fine structure of a low-frequency tone by phase-locking its response to the stimulus. Apart from sound localization, however, much about the role of this temporal information for signal processing in the brain remains unknown. Through psychoacoustic studies we provide direct evidence that humans employ temporal fine structure to discriminate between frequencies. To this end we construct tones that are based on a single frequency but in which, through the concatenation of wavelets, the phase changes randomly every few cycles. We then test the frequency discrimination of these phase-changing tones, of control tones without phase changes, and of short tones that consist of a single wavelet. For carrier frequencies below a few kilohertz we find that phase changes systematically worsen frequency discrimination. No such effect appears for higher carrier frequencies at which temporal information is not available in the central auditory system. © 2012 Reichenbach, Hudspeth.
CRIS-Team Scopus Importer:2021-02-25

Driven transport on parallel lanes with particle exclusion and obstruction - Melbinger, Anna; Reichenbach, Tobias; Franosch, Thomas; Frey, Erwin (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2011)
We investigate a driven two-channel system where particles on different lanes mutually obstruct each other's motion, extending an earlier model by Popkov and Peschel. This obstruction may occur in biological contexts due to steric hinderance where motor proteins carry cargos by "walking" on microtubules. Similarly, the model serves as a description for classical spin transport where charged particles with internal states move unidirectionally on a lattice. Three regimes of qualitatively different behavior are identified, depending on the strength of coupling between the lanes. For small and large coupling strengths the model can be mapped to a one-channel problem, whereas a rich phase behavior emerges for intermediate ones. We derive an approximate but quantitatively accurate theoretical description in terms of a one-site cluster approximation, and obtain insight into the phase behavior through the current-density relations combined with an extremal-current principle. Our results are confirmed by stochastic simulations. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2021-02-25

Dual contribution to amplification in the mammalian inner ear - Reichenbach, Tobias; Hudspeth, A. J. (Physical Review Letters, 2010)
The inner ear achieves a wide dynamic range of responsiveness by mechanically amplifying weak sounds. The enormous mechanical gain reported for the mammalian cochlea, which exceeds a factor of 4000, poses a challenge for theory. Here we show how such a large gain can result from an interaction between amplification by low-gain hair bundles and a pressure wave: hair bundles can amplify both their displacement per locally applied pressure and the pressure wave itself. A recently proposed ratchet mechanism, in which hair-bundle forces do not feed back on the pressure wave, delineates the two effects. Our analytical calculations with a WKB approximation agree with numerical solutions. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2021-02-25

Effect of visual input on syllable parsing in a computational model of a neural microcircuit for speech processing - Kulkarni, Anirudh; Kegler, Mikolaj; Reichenbach, Tobias (Journal of Neural Engineering, 2021)
Objective. Seeing a person talking can help us understand them, particularly in a noisy environment. However, how the brain integrates the visual information with the auditory signal to enhance speech comprehension remains poorly understood. Approach. Here we address this question in a computational model of a cortical microcircuit for speech processing. The model consists of an excitatory and an inhibitory neural population that together create oscillations in the theta frequency range. When stimulated with speech, the theta rhythm becomes entrained to the onsets of syllables, such that the onsets can be inferred from the network activity. We investigate how well the obtained syllable parsing performs when different types of visual stimuli are added. In particular, we consider currents related to the rate of syllables as well as currents related to the mouth-opening area of the talking faces. Main results. We find that currents that target the excitatory neuronal population can influence speech comprehension, both boosting it or impeding it, depending on the temporal delay and on whether the currents are excitatory or inhibitory. In contrast, currents that act on the inhibitory neurons do not impact speech comprehension significantly. Significance. Our results suggest neural mechanisms for the integration of visual information with the acoustic information in speech and make experimentally-testable predictions.
CRIS-Team WoS Importer:2021-10-29

Emotive Response to a Hybrid-Face Robot and Translation to Consumer Social Robots - Wairagkar, Maitreyee; Lima, Maria R.; Bazo, Daniel; Craig, Richard; Weissbart, Hugo; Etoundi, Appolinaire C.; Reichenbach, Tobias; Iyengar, Prashant; Vaswani, Sneh; James, Christopher; Barnaghi, Payam; Melhuish, Chris; et al. (IEEE Internet of Things, 2021)
We present the conceptual formulation, design, fabrication, control and commercial translation of an IoT enabled social robot as mapped through validation of human emotional response to its affective interactions. The robot design centres on a humanoid hybrid-face that integrates a rigid faceplate with a digital display to simplify conveyance of complex facial movements while providing the impression of three-dimensional depth. We map the emotions of the robot to specific facial feature parameters, characterise recognisability of archetypical facial expressions, and introduce pupil dilation as an additional degree of freedom for emotion conveyance. Human interaction experiments demonstrate the ability to effectively convey emotion from the hybrid-robot face to humans. Conveyance is quantified by studying neurophysiological electroencephalography (EEG) response to perceived emotional information as well as through qualitative interviews. Results demonstrate core hybrid-face robotic expressions can be discriminated by humans (80%+ recognition) and invoke face-sensitive neurophysiological event-related potentials such as N170 and Vertex Positive Potentials in EEG. The hybrid-face robot concept has been modified, implemented, and released by Emotix Inc in the commercial IoT robotic platform Miko (‘My Companion’), an affective robot currently in use for human-robot interaction with children. We demonstrate that human EEG responses to Miko emotions are comparative to that of the hybrid-face robot validating design modifications implemented for large scale distribution. Finally, interviews show above 90% expression recognition rates in our commercial robot. We conclude that simplified hybrid-face abstraction conveys emotions effectively and enhances human-robot interaction.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Affective Robot; Brain-Robot Interface; Electroencephalography; Emotional Response; Event-Related Potential; Face recognition; Faces; Facial Expression; Human-robot interaction; Human-Robot Interaction.; Internet of Things; Robot sensing systems; Robots

Enhancement of speech-in-noise comprehension through vibrotactile stimulation at the syllabic rate - Guilleminot, Pierre; Reichenbach, Tobias (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Speech unfolds over distinct temporal scales, in particular, those related to the rhythm of phonemes, syllables, and words. When a person listens to continuous speech, the syllabic rhythm is tracked by neural activity in the theta frequency range. The tracking plays a functional role in speech processing: Influencing the theta activity through transcranial current stimulation, for instance, can impact speech perception. The theta-band activity in the auditory cortex can also be modulated through the somatosensory system, but the effect on speech processing has remained unclear. Here, we show that vibrotactile feedback presented at the rate of syllables can modulate and, in fact, enhance the comprehension of a speech signal in background noise. The enhancement occurs when vibrotactile pulses occur at the perceptual center of the syllables, whereas a temporal delay between the vibrotactile signals and the speech stream can lead to a lower level of speech comprehension. We further investigate the neural mechanisms underlying the audiotactile integration through electroencephalographic (EEG) recordings. We find that the audiotactile stimulation modulates the neural response to the speech rhythm, as well as the neural response to the vibrotactile pulses. The modulations of these neural activities reflect the behavioral effects on speech comprehension. Moreover, we demonstrate that speech comprehension can be predicted by particular aspects of the neural responses. Our results evidence a role of vibrotactile information for speech processing and may have applications in future auditory prosthesis.
CRIS-Team Scopus Importer:2022-04-15
Keywords: audiotactile integration; EEG; speech-in-noise comprehension

Entropy production of cyclic population dynamics - Andrae, Benjamin; Cremer, Jonas; Reichenbach, Tobias; Frey, Erwin (Physical Review Letters, 2010)
Entropy serves as a central observable in equilibrium thermodynamics. However, many biological and ecological systems operate far from thermal equilibrium. Here we show that entropy production can characterize the behavior of such nonequilibrium systems. To this end we calculate the entropy production for a population model that displays nonequilibrium behavior resulting from cyclic competition. At a critical point the dynamics exhibits a transition from large, limit-cycle-like oscillations to small, erratic oscillations. We show that the entropy production peaks very close to the critical point and tends to zero upon deviating from it. We further provide analytical methods for computing the entropy production which agree excellently with numerical simulations. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2021-02-25

Estimation of the Neural Sources of the EEG-measured Speech-FFR using a Phenomenological Model of Auditory-nerve Fiber Responses - Auernheimer, Jonas; Reichenbach, Tobias (European Signal Processing Conference, 2024)
The frequency-following-response to continuous speech (speech-FFR) is a characteristic neural activity that emerges at the fundamental frequency of a speaker’s voice and can be measured by electroencephalography (EEG) and magnetoencephalography (MEG). Its spectrotemporal dynamics and neural sources encode important pitch information critical for reliable speech processing. EEG studies have found a peak latency of the speech-FFR at around 10 ms with putative subcortical origin while recent MEG studies identified additional cortical contributions to the speech-FFR driven by the carrier and the envelope modulations at higher frequencies. In this study, we examined the spatiotemporal dynamics of the speech-FFR at the fundamental frequency using linear modelling and inverse source localization. We found that the response mainly originates from subcortical sources with major contributions from the midbrain for the two implemented acoustic features, the fundamental waveform and higher frequency envelope modulations. Interestingly, the latter evoked some additional brainstem activity at latencies significantly later than the typical subcortical latency range. Our results confirm the subcortically-dominated nature of the EEG-measured speech-FFR while additional top-down modulation might be evident by recurring brainstem activity.
CRIS-Team Scopus Importer:2024-11-15
Keywords: EEG; Frequency-following-response (FFR); Fundamental frequency; Neural source localization; Speech-FFR

Frequency decoding of periodically timed action potentials through distinct activity patterns in a random neural network - Reichenbach, Tobias; Hudspeth, A. J. (New Journal of Physics, 2012)
Frequency discrimination is a fundamental task of the auditory system. The mammalian inner ear, or cochlea, provides a place code in which different frequencies are detected at different spatial locations. However, a temporal code based on spike timing is also available: action potentials evoked in an auditory-nerve fiber by a low-frequency tone occur at a preferred phase of the stimulus - they exhibit phase locking - and thus provide temporal information about the tone's frequency. Humans employ this temporal information for discrimination of low frequencies. How might such temporal information be read out in the brain? Here we employ statistical and numerical methods to demonstrate that recurrent random neural networks in which connections between neurons introduce characteristic time delays, and in which neurons require temporally coinciding inputs for spike initiation, can perform sharp frequency discrimination when stimulated with phase-locked inputs. Although the frequency resolution achieved by such networks is limited by the noise in phase locking, the resolution for realistic values reaches the tiny frequency difference of 0.2% that has been measured in humans. © IOP Publishing and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2021-02-25

Hair bundles of cochlear outer hair cells are shaped to minimize their fluid-dynamic resistance - Ciganovic, Nikola; Wolde-Kidan, Amanuel; Reichenbach, Tobias (Scientific Reports, 2017)
The mammalian sense of hearing relies on two types of sensory cells: Inner hair cells transmit the auditory stimulus to the brain, while outer hair cells mechanically modulate the stimulus through active feedback. Stimulation of a hair cell is mediated by displacements of its mechanosensitive hair bundle which protrudes from the apical surface of the cell into a narrow fluid-filled space between reticular lamina and tectorial membrane. While hair bundles of inner hair cells are of linear shape, those of outer hair cells exhibit a distinctive V-shape. The biophysical rationale behind this morphology, however, remains unknown. Here we use analytical and computational methods to study the fluid flow across rows of differently shaped hair bundles. We find that rows of V-shaped hair bundles have a considerably reduced resistance to crossflow, and that the biologically observed shapes of hair bundles of outer hair cells are near-optimal in this regard. This observation accords with the function of outer hair cells and lends support to the recent hypothesis that inner hair cells are stimulated by a net flow, in addition to the well-established shear flow that arises from shearing between the reticular lamina and the tectorial membrane.
CRIS-Team Scopus Importer:2021-02-25

Hearing Aids Do Not Alter Cortical Entrainment to Speech at Audible Levels in Mild-to-Moderately Hearing-Impaired Subjects - Vanheusden, Frederique J.; Kegler, Mikolaj; Ireland, Katie; Georga, Constantina; Simpson, David M.; Reichenbach, Tobias; Bell, Steven L. (Frontiers in Human Neuroscience, 2020)
Background: Cortical entrainment to speech correlates with speech intelligibility and attention to a speech stream in noisy environments. However, there is a lack of data on whether cortical entrainment can help in evaluating hearing aid fittings for subjects with mild to moderate hearing loss. One particular problem that may arise is that hearing aids may alter the speech stimulus during (pre-)processing steps, which might alter cortical entrainment to the speech. Here, the effect of hearing aid processing on cortical entrainment to running speech in hearing impaired subjects was investigated. Methodology: Seventeen native English-speaking subjects with mild-to-moderate hearing loss participated in the study. Hearing function and hearing aid fitting were evaluated using standard clinical procedures. Participants then listened to a 25-min audiobook under aided and unaided conditions at 70 dBA sound pressure level (SPL) in quiet conditions. EEG data were collected using a 32-channel system. Cortical entrainment to speech was evaluated using decoders reconstructing the speech envelope from the EEG data. Null decoders, obtained from EEG and the time-reversed speech envelope, were used to assess the chance level reconstructions. Entrainment in the delta- (1–4 Hz) and theta- (4–8 Hz) band, as well as wideband (1–20 Hz) EEG data was investigated. Results: Significant cortical responses could be detected for all but one subject in all three frequency bands under both aided and unaided conditions. However, no significant differences could be found between the two conditions in the number of responses detected, nor in the strength of cortical entrainment. The results show that the relatively small change in speech input provided by the hearing aid was not sufficient to elicit a detectable change in cortical entrainment. Conclusion: For subjects with mild to moderate hearing loss, cortical entrainment to speech in quiet at an audible level is not affected by hearing aids. These results clear the pathway for exploring the potential to use cortical entrainment to running speech for evaluating hearing aid fitting at lower speech intensities (which could be inaudible when unaided), or using speech in noise conditions.
CRIS-Team Scopus Importer:2021-02-25
Keywords: cortical entrainment; electroencephalography; hearing aid evaluation; hearing impairment; speech detection

Individual differences in the attentional modulation of the human auditory brainstem response to speech inform on speech-in-noise deficits - Saiz-Alia, Marina; Forte, Antonio Elia; Reichenbach, Tobias (Scientific Reports, 2019)
People with normal hearing thresholds can nonetheless have difficulty with understanding speech in noisy backgrounds. The origins of such supra-threshold hearing deficits remain largely unclear. Previously we showed that the auditory brainstem response to running speech is modulated by selective attention, evidencing a subcortical mechanism that contributes to speech-in-noise comprehension. We observed, however, significant variation in the magnitude of the brainstem’s attentional modulation between the different volunteers. Here we show that this variability relates to the ability of the subjects to understand speech in background noise. In particular, we assessed 43 young human volunteers with normal hearing thresholds for their speech-in-noise comprehension. We also recorded their auditory brainstem responses to running speech when selectively attending to one of two competing voices. To control for potential peripheral hearing deficits, and in particular for cochlear synaptopathy, we further assessed noise exposure, the temporal sensitivity threshold, the middle-ear muscle reflex, and the auditory-brainstem response to clicks in various levels of background noise. These tests did not show evidence for cochlear synaptopathy amongst the volunteers. Furthermore, we found that only the attentional modulation of the brainstem response to speech was significantly related to speech-in-noise comprehension. Our results therefore evidence an impact of top-down modulation of brainstem activity on the variability in speech-in-noise comprehension amongst the subjects.
CRIS-Team Scopus Importer:2021-02-25

Minimal basilar membrane motion in low-frequency hearing - Warren, Rebecca L.; Ramamoorthy, Sripriya; Ciganovic, Nikola; Zhang, Yuan; Wilson, Teresa M.; Petrie, Tracy; Wang, Ruikang K.; Jacques, Steven L.; Reichenbach, Tobias; Nuttall, Alfred L.; Fridberger, Anders (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Low-frequency hearing is critically important for speech and music perception, but no mechanical measurements have previously been available from inner ears with intact low-frequency parts. These regions of the cochlea may function in ways different from the extensively studied high-frequency regions, where the sensory outer hair cells produce force that greatly increases the soundevoked vibrations of the basilar membrane. We used laser interferometry in vitro and optical coherence tomography in vivo to study the low-frequency part of the Guinea pig cochlea, and found that sound stimulation caused motion of a minimal portion of the basilar membrane. Outside the region of peak movement, an exponential decline in motion amplitude occurred across the basilar membrane. The moving region had different dependence on stimulus frequency than the vibrations measured near the mechanosensitive stereocilia. This behavior differs substantially from the behavior found in the extensively studied high-frequency regions of the cochlea.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Basilar membrane; Hair cells; Hearing; Optical coherence tomography

Mobility-dependent selection of competing strategy associations - Dobrinevski, Alexander; Alava, Mikko; Reichenbach, Tobias; Frey, Erwin (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2014)
Standard models of population dynamics focus on the interaction, survival, and extinction of the competing species individually. Real ecological systems, however, are characterized by an abundance of species (or strategies, in the terminology of evolutionary-game theory) that form intricate, complex interaction networks. The description of the ensuing dynamics may be aided by studying associations of certain strategies rather than individual ones. Here we show how such a higher-level description can bear fruitful insight. Motivated from different strains of colicinogenic Escherichia coli bacteria, we investigate a four-strategy system which contains a three-strategy cycle and a neutral alliance of two strategies. We find that the stochastic, spatial model exhibits a mobility-dependent selection of either the three-strategy cycle or of the neutral pair. We analyze this intriguing phenomenon numerically and analytically. © 2014 American Physical Society.
CRIS-Team Scopus Importer:2021-02-25

Modelling the effects of transcranial alternating current stimulation on the neural encoding of speech in noise - Kegler, Mikolaj; Reichenbach, Tobias (NeuroImage, 2021)
Transcranial alternating current stimulation (tACS) can non-invasively modulate neuronal activity in the cerebral cortex, in particular at the frequency of the applied stimulation. Such modulation can matter for speech processing, since the latter involves the tracking of slow amplitude fluctuations in speech by cortical activity. tACS with a current signal that follows the envelope of a speech stimulus has indeed been found to influence the cortical tracking and to modulate the comprehension of the speech in background noise. However, how exactly tACS influences the speech-related cortical activity, and how it causes the observed effects on speech comprehension, remains poorly understood. A computational model for cortical speech processing in a biophysically plausible spiking neural network has recently been proposed. Here we extended the model to investigate the effects of different types of stimulation waveforms, similar to those previously applied in experimental studies, on the processing of speech in noise. We assessed in particular how well speech could be decoded from the neural network activity when paired with the exogenous stimulation. We found that, in the absence of current stimulation, the speech-in-noise decoding accuracy was comparable to the comprehension of speech in background noise of human listeners. We further found that current stimulation could alter the speech decoding accuracy by a few percent, comparable to the effects of tACS on speech-in-noise comprehension. Our simulations further allowed us to identify the parameters for the stimulation waveforms that yielded the largest enhancement of speech-in-noise encoding. Our model thereby provides insight into the potential neural mechanisms by which weak alternating current stimulation may influence speech comprehension and allows to screen a large range of stimulation waveforms for their effect on speech processing.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Computational modelling; Speech processing; Spiking neural networks; Transcranial alternating current stimulation

Modulation of Speech-in-Noise Comprehension through Transcranial Current Stimulation with the Phase-Shifted Speech Envelope - Kadir, Shabnam; Kaza, Chrysoula; Weissbart, Hugo; Reichenbach, Tobias (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2020)
Neural activity tracks the envelope of a speech signal at latencies from 50 ms to 300 ms. Modulating this neural tracking through transcranial alternating current stimulation influences speech comprehension. Two important variables that can affect this modulation are the latency and the phase of the stimulation with respect to the sound. While previous studies have found an influence of both variables on speech comprehension, the interaction between both has not yet been measured. We presented 17 subjects with speech in noise coupled with simultaneous transcranial alternating current stimulation. The currents were based on the envelope of the target speech but shifted by different phases, as well as by two temporal delays of 100 ms and 250 ms. We also employed various control stimulations, and assessed the signal-to-noise ratio at which the subject understood half of the speech. We found that, at both latencies, speech comprehension is modulated by the phase of the current stimulation. However, the form of the modulation differed between the two latencies. Phase and latency of neurostimulation have accordingly distinct influences on speech comprehension. The different effects at the latencies of 100 ms and 250 ms hint at distinct neural processes for speech processing.
CRIS-Team Scopus Importer:2021-02-25
Keywords: speech envelope; speech-in-noise comprehension; Transcranial current stimulation

Neural Speech Tracking in the Theta and in the Delta Frequency Band Differentially Encode Clarity and Comprehension of Speech in Noise - Etard, Octave; Reichenbach, Tobias (The Journal of Neuroscience, 2019)
Humans excel at understanding speech even in adverse conditions such as background noise. Speech processing may be aided by cortical activity in the delta and theta frequency bands, which have been found to track the speech envelope. However, the rhythm of non-speech sounds is tracked by cortical activity as well. It therefore remains unclear which aspects of neural speech tracking represent the processing of acoustic features, related to the clarity of speech, and which aspects reflect higher-level linguistic processing related to speech comprehension. Here we disambiguate the roles of cortical tracking for speech clarity and comprehension through recording EEG responses to native and foreign language in different levels of background noise, for which clarity and comprehension vary independently. We then use a both a decoding and an encoding approach to relate clarity and comprehension to the neural responses. We find that cortical tracking in the theta frequency band is mainly correlated to clarity, whereas the delta band contributes most to speech comprehension. Moreover, we uncover an early neural component in the delta band that informs on comprehension and that may reflect a predictive mechanism for language processing. Our results disentangle the functional contributions of cortical speech tracking in the delta and theta bands to speech processing. They also show that both speech clarity and comprehension can be accurately decoded from relatively short segments of EEG recordings, which may have applications in future mind-controlled auditory prosthesis.SIGNIFICANCE STATEMENT Speech is a highly complex signal whose processing requires analysis from lower-level acoustic features to higher-level linguistic information. Recent work has shown that neural activity in the delta and theta frequency bands track the rhythm of speech, but the role of this tracking for speech processing remains unclear. Here we disentangle the roles of cortical entrainment in different frequency bands and at different temporal lags for speech clarity, reflecting the acoustics of the signal, and speech comprehension, related to linguistic processing. We show that cortical speech tracking in the theta frequency band encodes mostly speech clarity, and thus acoustic aspects of the signal, whereas speech tracking in the delta band encodes the higher-level speech comprehension.
CRIS-Team Scopus Importer:2021-02-25
Keywords: envelope tracking; neural oscillations; speech comprehension; speech processing

No Evidence of Attentional Modulation of the Neural Response to the Temporal Fine Structure of Continuous Musical Pieces - Etard, Octave; Messaoud, Rémy Ben; Gaugain, Gabriel; Reichenbach, Tobias (Journal of Cognitive Neuroscience, 2022)
Speech and music are spectrotemporally complex acoustic signals that are highly relevant for humans. Both contain a temporal fine structure that is encoded in the neural responses of subcortical and cortical processing centers. The subcortical response to the temporal fine structure of speech has recently been shown to be modulated by selective attention to one of two competing voices. Music similarly often consists of several simultaneous melodic lines, and a listener can selectively attend to a particular one at a time. However, the neural mechanisms that enable such selective attention remain largely enigmatic, not least since most investigations to date have focused on short and simplified musical stimuli. Here, we studied the neural encoding of classical musical pieces in human volunteers, using scalp EEG recordings. We presented volunteers with continuous musical pieces composed of one or two instruments. In the latter case, the participants were asked to selectively attend to one of the two competing instruments and to perform a vibrato identification task. We used linear encoding and decoding models to relate the recorded EEG activity to the stimulus waveform. We show that we can measure neural responses to the temporal fine structure of melodic lines played by one single instrument, at the population level as well as for most individual participants. The neural response peaks at a latency of 7.6 msec and is not measurable past 15 msec. When analyzing the neural responses to the temporal fine structure elicited by competing instruments, we found no evidence of attentional modulation. We observed, however, that low-frequency neural activity exhibited a modulation consistent with the behavioral task at latencies from 100 to 160 msec, in a similar manner to the attentional modulation observed in continuous speech (N100). Our results show that, much like speech, the temporal fine structure of music is tracked by neural activity. In contrast to speech, however, this response appears unaffected by selective attention in the context of our experiment.
CRIS-Team Scopus Importer:2022-02-11

No Evidence of Musical Training Influencing the Cortical Contribution to the Speech-Frequency-Following Response and Its Modulation through Selective Attention - Riegel, Jasmin; Schüller, Alina; Reichenbach, Tobias (eNeuro, 2024)
Musicians can have better abilities to understand speech in adverse condition such as background noise than non-musicians. However, the neural mechanisms behind such enhanced behavioral performances remain largely unclear. Studies have found that the subcortical frequency-following response to the fundamental frequency of speech and its higher harmonics (speech-FFR) may be involved since it is larger in people with musical training than in those without. Recent research has shown that the speech-FFR consists of a cortical contribution in addition to the subcortical sources. Both the subcortical and the cortical contribution are modulated by selective attention to one of two competing speakers. However, it is unknown whether the strength of the cortical contribution to the speech-FFR, or its attention modulation, is influenced by musical training. Here we investigate these issues through magnetoencephalographic (MEG) recordings of 52 subjects (18 musicians, 25 non-musicians, and 9 neutral participants) listening to two competing male speakers while selectively attending one of them. The speech-in-noise comprehension abilities of the participants were not assessed. We find that musicians and non-musicians display comparable cortical speech-FFRs and additionally exhibit similar subjectto-subject variability in the response. Furthermore, we also do not observe a difference in the modulation of the neural response through selective attention between musicians and non-musicians. Moreover, when assessing whether the cortical speech-FFRs are influenced by particular aspects of musical training, no significant effects emerged. Taken together, we did not find any effect of musical training on the cortical speech-FFR.
CRIS-Team Scopus Importer:2024-09-20

Otoacoustic emission through waves on Reissner's membrane and bone deformation - Reichenbach, Tobias (Proceedings of Forum Acusticum, 2014)
The inner ear acts not only as a detector of sound, but can produce sound itself. These otoacoustic emissions are generated by an active process in the inner ear. The active process leads to a nonlinearity that produces distortion that is emitted as sound from the ear. How such a distortion propagates from its generation site within the inner ear back to the middle ear remains, however, unclear. Here we describe two novel modes of wave propagation in the cochlea, namely a wave on the elastic Reissner's membrane as well as a wave of deformation of the cochlear bone. Each mode can explain a distinct component of otoacoustic emissions. The cochlear-bone deformation can also underlie bone conduction, the phenomenon by which we can hear a vibration of the skull as sound.
CRIS-Team Scopus Importer:2021-02-25

Otoacoustic emission through waves on Reissner's membrane - Reichenbach, Tobias; Stefanovic, Aleksandra; Nin, Fumiaki; Hudspeth, A. J. (AIP Conference Proceedings, 2015)
Otoacoustic emissions are a striking manifestation of mechanical activity within the cochlea. Recent experimental work has stirred a controversy concerning how these mechanical signals propagate outward to the middle ear, from which they are emitted as airborne sounds. Here we show that Reissner's membrane, an elastic structure inside the inner ear, can sustain wave propagation and can therefore transmit otoacoustic emissions from inside the cochlea to the middle ear. We first develop a theoretical description for wave propagation on the parallel basilar and Reissner's membranes. We then describe experimental measurement of the predicted Reissner's membrane wave and its role in distortion-product otoacoustic emissions.
CRIS-Team Scopus Importer:2021-02-25

Phase-locking of Neural Activity to the Envelope of Speech in the Delta Frequency Band Reflects Differences between Word Lists and Sentences - Mohammadi, Yousef; Graversen, Carina; Østergaard, Jan; Andersen, Ole Kaeseler; Reichenbach, Tobias (Journal of Cognitive Neuroscience, 2023)
The envelope of a speech signal is tracked by neural activity in the cerebral cortex. The cortical tracking occurs mainly in two frequency bands, theta (4–8 Hz) and delta (1–4 Hz). Tracking in the faster theta band has been mostly associated with lower-level acoustic processing, such as the parsing of syllables, whereas the slower tracking in the delta band relates to higher-level linguistic information of words and word sequences. However, much regarding the more specific association between cortical tracking and acoustic as well as linguistic processing remains to be uncovered. Here, we recorded EEG responses to both meaningful sentences and random word lists in different levels of signal-to-noise ratios (SNRs) that lead to different levels of speech comprehension as well as listening effort. We then related the neural signals to the acoustic stimuli by computing the phase-locking value (PLV) between the EEG recordings and the speech envelope. We found that the PLV in the delta band increases with increasing SNR for sentences but not for the random word lists, showing that the PLV in this frequency band reflects linguistic information. When attempting to disentangle the effects of SNR, speech comprehension, and listening effort, we observed a trend that the PLV in the delta band might reflect listening effort rather than the other two variables, although the effect was not statistically significant. In summary, our study shows that the PLV in the delta band reflects linguistic information and might be related to listening effort.
CRIS-Team Scopus Importer:2023-12-15

Relating EEG Recordings to Speech Using Envelope Tracking and The Speech-FFR - Thornton, Mike; Mandic, Danilo; Reichenbach, Tobias (ICASSP, IEEE International Conference on Acoustics, Speech and Signal Processing - Proceedings, 2023)
During speech perception, a listener's electroencephalogram (EEG) reflects acoustic-level processing as well as higher-level cognitive factors such as speech comprehension and attention. However, decoding speech from EEG recordings is challenging due to the low signal-to-noise ratios of EEG signals. We report on an approach developed for the ICASSP 2023 'Auditory EEG Decoding' Signal Processing Grand Challenge. A simple ensembling method is shown to considerably improve upon the baseline decoder performance. Even higher classification rates are achieved by jointly decoding the speech-evoked frequency-following response and responses to the temporal envelope of speech, as well as by fine-tuning the decoders to individual subjects. Our results could have applications in the diagnosis of hearing disorders or in cognitively steered hearing aids.
CRIS-Team Scopus Importer:2023-12-01
Keywords: deep learning; EEG decoding; speech

Robust decoding of the speech envelope from EEG recordings through deep neural networks - Thornton, Mike; Mandic, Danilo; Reichenbach, Tobias (Journal of Neural Engineering, 2022)
Objective. Smart hearing aids which can decode the focus of a user's attention could considerably improve comprehension levels in noisy environments. Methods for decoding auditory attention from electroencapholography (EEG) have attracted considerable interest for this reason. Recent studies suggest that the integration of deep neural networks (DNNs) into existing auditory attention decoding (AAD) algorithms is highly beneficial, although it remains unclear whether these enhanced algorithms can perform robustly in different real-world scenarios. Therefore, we sought to characterise the performance of DNNs at reconstructing the envelope of an attended speech stream from EEG recordings in different listening conditions. In addition, given the relatively sparse availability of EEG data, we investigate possibility of applying subject-independent algorithms to EEG recorded from unseen individuals. Approach. Both linear models and nonlinear DNNs were employed to decode the envelope of clean speech from EEG recordings, with and without subject-specific information. The mean behaviour, as well as the variability of the reconstruction, was characterised for each model. We then trained subject-specific linear models and DNNs to reconstruct the envelope of speech in clean and noisy conditions, and investigated how well they performed in different listening scenarios. We also established that these models can be used to decode auditory attention in competing-speaker scenarios. Main results. The DNNs offered a considerable advantage over their linear analogue at reconstructing the envelope of clean speech. This advantage persisted even when subject-specific information was unavailable at the time of training. The same DNN architectures generalised to a distinct dataset, which contained EEG recorded under a variety of listening conditions. In competing-speakers and speech-in-noise conditions, the DNNs significantly outperformed the linear models. Finally, the DNNs offered a considerable improvement over the linear approach at decoding auditory attention in competing-speakers scenarios. Significance. We present the first detailed study into the extent to which DNNs can be employed for reconstructing the envelope of an attended speech stream. We conclusively demonstrate that DNNs improve the reconstruction of the attended speech envelope. The variance of the reconstruction error is shown to be similar for both DNNs and the linear model. DNNs therefore show promise for real-world AAD, since they perform well in multiple listening conditions and generalise to data recorded from unseen participants.
CRIS-Team WoS Importer:2022-07-22

Selective attention in the brainstem and speech-in-noise comprehension - Saiz-Alia, Marina; Forte, Antonio Elia; Reichenbach, Tobias (Proceedings of the International Congress on Acoustics, 2019)
Understanding speech in noise is a challenging task. Moreover, the ability to understand speech in background noise varies considerably from person to person, even for people that have normal audiograms and hence no measurable hearing loss. Recently we proposed a method for measuring the brainstem's response to natural non-repetitive speech and showed that this response is modulated by selective attention to one of two competing speakers. Here we investigate to what extent this brainstem response varies from subject to subject. We find significant between-subject variation in the amplitude of the brainstem response to continuous speech, in its latency, signal-to-noise-ratio, as well as in its modulation by selective attention. This variability may result from impairments in the auditory periphery, such a cochlear synaptopathy, as well as from damages of the neural pathways in the brainstem and in the central nervous system that are responsible for sound processing, and may potentially lead to deficits with speech-in-noise comprehension.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Auditory brainstem response; Selective attention; Speech processing

Speech Auditory Brainstem Responses in Adult Hearing Aid Users: Effects of Aiding and Background Noise, and Prediction of Behavioral Measures - Binkhamis, Ghada; Forte, Antonio Elia; Reichenbach, Tobias; O'Driscoll, Martin; Kluk, Karolina (Trends in Hearing, 2019)
Evaluation of patients who are unable to provide behavioral responses on standard clinical measures is challenging due to the lack of standard objective (non-behavioral) clinical audiological measures that assess the outcome of an intervention (e.g., hearing aids). Brainstem responses to short consonant-vowel stimuli (speech-auditory brainstem responses [speech-ABRs]) have been proposed as a measure of subcortical encoding of speech, speech detection, and speech-in-noise performance in individuals with normal hearing. Here, we investigated the potential application of speech-ABRs as an objective clinical outcome measure of speech detection, speech-in-noise detection and recognition, and self-reported speech understanding in 98 adults with sensorineural hearing loss. We compared aided and unaided speech-ABRs, and speech-ABRs in quiet and in noise. In addition, we evaluated whether speech-ABR F0 encoding (obtained from the complex cross-correlation with the 40 ms [da] fundamental waveform) predicted aided behavioral speech recognition in noise or aided self-reported speech understanding. Results showed that (a) aided speech-ABRs had earlier peak latencies, larger peak amplitudes, and larger F0 encoding amplitudes compared to unaided speech-ABRs; (b) the addition of background noise resulted in later F0 encoding latencies but did not have an effect on peak latencies and amplitudes or on F0 encoding amplitudes; and (c) speech-ABRs were not a significant predictor of any of the behavioral or self-report measures. These results show that speech-ABR F0 encoding is not a good predictor of speech-in-noise recognition or self-reported speech understanding with hearing aids. However, our results suggest that speech-ABRs may have potential for clinical application as an objective measure of speech detection with hearing aids.
CRIS-Team Scopus Importer:2021-02-25
Keywords: aided speech-ABR; background noise; hearing aid; Speech-ABR; speech-in-noise performance

Speech-DPOAEs for probing speech processing in the inner ear - Saiz-Alia, Marina; Miller, Peter; Reichenbach, Tobias (AIP Conference Proceedings, 2024)
Speech is a complex real-world stimulus that consists of time-varying contributions in many frequency bands. The inner ear, or cochlea, not only transduces the acoustic vibrations into electrical signals, but also spatially segregates the acoustic waveform into different frequency components, as well as mechanically amplifies the vibrations in frequency bands where the amplitude is low. This processing of the speech signal can potentially be controlled through efferent nerve fibers that extend from higher processing centers in the brain to the cochlea. However, we are currently lacking methodological tools to non-invasively investigate the putative role of top-down feedback on speech processing in humans. Here we develop such a method that builds on distortion-product otoacoustic emissions (DPOAEs) related to the temporal fine structure of the voiced parts of speech (speech-DPOAEs).
CRIS-Team Scopus Importer:2024-03-22

Speech-Driven Facial Animations Improve Speech-in-Noise Comprehension of Humans - Varano, Enrico; Vougioukas, Konstantinos; Ma, Pingchuan; Petridis, Stavros; Pantic, Maja; Reichenbach, Tobias (Frontiers in Neuroscience, 2022)
Understanding speech becomes a demanding task when the environment is noisy. Comprehension of speech in noise can be substantially improved by looking at the speaker’s face, and this audiovisual benefit is even more pronounced in people with hearing impairment. Recent advances in AI have allowed to synthesize photorealistic talking faces from a speech recording and a still image of a person’s face in an end-to-end manner. However, it has remained unknown whether such facial animations improve speech-in-noise comprehension. Here we consider facial animations produced by a recently introduced generative adversarial network (GAN), and show that humans cannot distinguish between the synthesized and the natural videos. Importantly, we then show that the end-to-end synthesized videos significantly aid humans in understanding speech in noise, although the natural facial motions yield a yet higher audiovisual benefit. We further find that an audiovisual speech recognizer (AVSR) benefits from the synthesized facial animations as well. Our results suggest that synthesizing facial motions from speech can be used to aid speech comprehension in difficult listening environments.
CRIS-Team Scopus Importer:2022-01-28
Keywords: audiovisual integration; facial animation; generative adversarial network (GAN); speech in noise; speech perception

Spoken word recognition enhancement due to preceding synchronized beats compared to unsynchronized or Unrhythmic beats - Sidiras, Christos; Iliadou, Vasiliki; Nimatoudis, Ioannis; Reichenbach, Tobias; Bamiou, Doris-Eva (Frontiers in Neuroscience, 2017)
The relation between rhythm and language has been investigated over the last decades, with evidence that these share overlapping perceptual mechanisms emerging from several different strands of research. The dynamic Attention Theory posits that neural entrainment to musical rhythm results in synchronized oscillations in attention, enhancing perception of other events occurring at the same rate. In this study, this prediction was tested in 10 year-old children by means of a psychoacoustic speech recognition in babble paradigm. It was hypothesized that rhythm effects evoked via a short isochronous sequence of beats would provide optimal word recognition in babble when beats and word are in sync. We compared speech recognition in babble performance in the presence of isochronous and in sync vs. non-isochronous or out of sync sequence of beats. Results showed that (a) word recognition was the best when rhythm and word were in sync, and (b) the effect was not uniform across syllables and gender of subjects. Our results suggest that pure tone beats affect speech recognition at early levels of sensory or phonemic processing.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Auditory processing; Dynamic attention theory; Hearing; Neural oscillations; Psychoacoustics; Rhythm; Speech processing; Speech segmentation

Static length changes of cochlear outer hair cells can tune low-frequency hearing - Ciganovic, Nikola; Warren, Rebecca L.; Keceli, Batu; Jacob, Stefan; Fridberger, Anders; Reichenbach, Tobias (PLoS Computational Biology, 2018)
The cochlea not only transduces sound-induced vibration into neural spikes, it also amplifies weak sound to boost its detection. Actuators of this active process are sensory outer hair cells in the organ of Corti, whereas the inner hair cells transduce the resulting motion into electric signals that propagate via the auditory nerve to the brain. However, how the outer hair cells modulate the stimulus to the inner hair cells remains unclear. Here, we combine theoretical modeling and experimental measurements near the cochlear apex to study the way in which length changes of the outer hair cells deform the organ of Corti. We develop a geometry-based kinematic model of the apical organ of Corti that reproduces salient, yet counter-intuitive features of the organ’s motion. Our analysis further uncovers a mechanism by which a static length change of the outer hair cells can sensitively tune the signal transmitted to the sensory inner hair cells. When the outer hair cells are in an elongated state, stimulation of inner hair cells is largely inhibited, whereas outer hair cell contraction leads to a substantial enhancement of sound-evoked motion near the hair bundles. This novel mechanism for regulating the sensitivity of the hearing organ applies to the low frequencies that are most important for the perception of speech and music. We suggest that the proposed mechanism might underlie frequency discrimination at low auditory frequencies, as well as our ability to selectively attend auditory signals in noisy surroundings.
CRIS-Team Scopus Importer:2021-02-25

Steady streaming as a method for drug delivery to the inner ear - Sumner, Laura; Mestel, Jonathan; Reichenbach, Tobias (Scientific Reports, 2021)
The inner ear, or cochlea, is a fluid-filled organ housing the mechanosensitive hair cells. Sound stimulation is relayed to the hair cells through waves that propagate on the elastic basilar membrane. Sensorineural hearing loss occurs from damage to the hair cells and cannot currently be cured. Although drugs have been proposed to prevent damage or restore functionality to hair cells, a difficulty with such treatments is ensuring adequate drug delivery to the cells. Because the cochlea is encased in the temporal bone, it can only be accessed from its basal end. However, the hair cells that are responsible for detecting speech-frequency sounds reside at the opposite, apical end. In this paper we show that steady streaming can be used to transport drugs along the cochlea. Steady streaming is a nonlinear process that accompanies many fluctuating fluid motions, including the sound-evoked waves in the inner ear. We combine an analytical approximation for the waves in the cochlea with computational fluid dynamic simulations to demonstrate that the combined steady streaming effects of several different frequencies can transport drugs from the base of the cochlea further towards the apex. Our results therefore show that multi-frequency sound stimulation can serve as a non-invasive method to transport drugs efficiently along the cochlea.
CRIS-Team Scopus Importer:2021-02-25

The auditory-brainstem response to continuous, non-repetitive speech is modulated by the speech envelope and reflects speech processing - Reichenbach, Chagit S.; Braiman, Chananel; Schiff, Nicholas D.; Hudspeth, A. J.; Reichenbach, Tobias (Frontiers in Computational Neuroscience, 2016)
The auditory-brainstem response (ABR) to short and simple acoustical signals is an important clinical tool used to diagnose the integrity of the brainstem. The ABR is also employed to investigate the auditory brainstem in a multitude of tasks related to hearing, such as processing speech or selectively focusing on one speaker in a noisy environment. Such research measures the response of the brainstem to short speech signals such as vowels or words. Because the voltage signal of the ABR has a tiny amplitude, several hundred to a thousand repetitions of the acoustic signal are needed to obtain a reliable response. The large number of repetitions poses a challenge to assessing cognitive functions due to neural adaptation. Here we show that continuous, non-repetitive speech, lasting several minutes, may be employed to measure the ABR. Because the speech is not repeated during the experiment, the precise temporal form of the ABR cannot be determined. We show, however, that important structural features of the ABR can nevertheless be inferred. In particular, the brainstem responds at the fundamental frequency of the speech signal, and this response is modulated by the envelope of the voiced parts of speech. We accordingly introduce a novel measure that assesses the ABR as modulated by the speech envelope, at the fundamental frequency of speech and at the characteristic latency of the response. This measure has a high signal-to-noise ratio and can hence be employed effectively to measure the ABR to continuous speech. We use this novel measure to show that the ABR is weaker to intelligible speech than to unintelligible, time-reversed speech. The methods presented here can be employed for further research on speech processing in the auditory brainstem and can lead to the development of future clinical diagnosis of brainstem function.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Auditory brainstem response (ABR); Fundamental frequency; Hearing; Speech envelope; Speech processing

The Early Subcortical Response at the Fundamental Frequency of Speech Is Temporally Separated from Later Cortical Contributions. - Schüller, Alina; Schilling, Achim; Krauß, Patrick; Reichenbach, Tobias (Journal of Cognitive Neuroscience, 2024)
Most parts of speech are voiced, exhibiting a degree of periodicity with a fundamental frequency and many higher harmonics. Some neural populations respond to this temporal fine structure, in particular at the fundamental frequency. This frequency-following response to speech consists of both subcortical and cortical contributions and can be measured through EEG as well as through magnetoencephalography (MEG), although both differ in the aspects of neural activity that they capture: EEG is sensitive to both radial and tangential sources as well as to deep sources, whereas MEG is more restrained to the measurement of tangential and superficial neural activity. EEG responses to continuous speech have shown an early subcortical contribution, at a latency of around 9 msec, in agreement with MEG measurements in response to short speech tokens, whereas MEG responses to continuous speech have not yet revealed such an early component. Here, we analyze MEG responses to long segments of continuous speech. We find an early subcortical response at latencies of 4-11 msec, followed by later right-lateralized cortical activities at delays of 20-58 msec as well as potential subcortical activities. Our results show that the early subcortical component of the FFR to continuous speech can be measured from MEG in populations of participants and that its latency agrees with that measured with EEG. They furthermore show that the early subcortical component is temporally well separated from later cortical contributions, enabling an independent assessment of both components toward further aspects of speech processing.
EVALuna2:574185

The edge of neutral evolution in social dilemmas - Cremer, Jonas; Reichenbach, Tobias; Frey, Erwin (New Journal of Physics, 2009)
The functioning of animal as well as human societies fundamentally relies on cooperation. Yet, defection is often favorable for the selfish individual, and social dilemmas arise. Selection by individuals' fitness, usually the basic driving force of evolution, quickly eliminates cooperators. However, evolution is also governed by fluctuations that can be of greater importance than fitness differences, and can render evolution effectively neutral. Here, we investigate the effects of selection versus fluctuations in social dilemmas. By studying the mean extinction times of cooperators and defectors, a variable sensitive to fluctuations, we are able to identify and quantify an emerging 'edge of neutral evolution' that delineates regimes of neutral and Darwinian evolution. Our results reveal that cooperation is significantly maintained in the neutral regimes. In contrast, the classical predictions of evolutionary game theory, where defectors beat cooperators, are recovered in the Darwinian regimes. Our studies demonstrate that fluctuations can provide a surprisingly simple way to partly resolve social dilemmas. Our methods are generally applicable to estimate the role of random drift in evolutionary dynamics. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2021-02-25

The human auditory brainstem response to running speech reveals a subcortical mechanism for selective attention - Forte, Antonio Elia; Etard, Octave; Reichenbach, Tobias (eLife, 2017)
Humans excel at selectively listening to a target speaker in background noise such as competing voices. While the encoding of speech in the auditory cortex is modulated by selective attention, it remains debated whether such modulation occurs already in subcortical auditory structures. Investigating the contribution of the human brainstem to attention has, in particular, been hindered by the tiny amplitude of the brainstem response. Its measurement normally requires a large number of repetitions of the same short sound stimuli, which may lead to a loss of attention and to neural adaptation. Here we develop a mathematical method to measure the auditory brainstem response to running speech, an acoustic stimulus that does not repeat and that has a high ecological validity. We employ this method to assess the brainstem’s activity when a subject listens to one of two competing speakers, and show that the brainstem response is consistently modulated by attention.
CRIS-Team Scopus Importer:2021-02-25

The Impact of Selective Attention and Musical Training on the Cortical Speech Tracking in the Delta and Theta Frequency Bands - Schüller, Alina; Mücke, Annika; Riegel, Jasmin; Reichenbach, Tobias (Journal of Cognitive Neuroscience, 2025)
Oral communication regularly takes place amidst background noise, requiring the ability to selectively attend to a target speech stream. Musical training has been shown to be beneficial for this task. Regarding the underlying neural mechanisms, recent studies showed that the speech envelope is tracked by neural activity in auditory cortex, which plays a role in the neural processing of speech, including speech in noise. The neural tracking occurs predominantly in two frequency bands, the delta and the theta bands. However, much regarding the specifics of these neural responses, as well as their modulation through musical training, still remain unclear. Here, we investigated the delta- and theta-band cortical tracking of the speech envelope of target and distractor speech using magnetoencephalography (MEG) recordings. We thereby assessed both musicians and nonmusicians to explore potential differences between these groups. The cortical speech tracking was quantified through source-reconstructing the MEG data and subsequently relating the speech envelope in a certain frequency band to the MEG data using linear models. We thereby found the theta-band tracking to be dominated by early responses with comparable magnitudes for target and distractor speech, whereas the delta band tracking exhibited both earlier and later responses that were modulated by selective attention. Almost no significant differences emerged in the neural responses between musicians and nonmusicians. Our findings show that only the speech tracking in the delta but not in the theta band contributes to selective attention, but that this mechanism is essentially unaffected by musical training.
CRIS-Team Scopus Importer:2025-02-14

The neural response at the fundamental frequency of speech is modulated by word-level acoustic and linguistic information - Kegler, Mikolaj; Weissbart, Hugo; Reichenbach, Tobias (Frontiers in Neuroscience, 2022)
Spoken language comprehension requires rapid and continuous integration of information, from lower-level acoustic to higher-level linguistic features. Much of this processing occurs in the cerebral cortex. Its neural activity exhibits, for instance, correlates of predictive processing, emerging at delays of a few 100 ms. However, the auditory pathways are also characterized by extensive feedback loops from higher-level cortical areas to lower-level ones as well as to subcortical structures. Early neural activity can therefore be influenced by higher-level cognitive processes, but it remains unclear whether such feedback contributes to linguistic processing. Here, we investigated early speech-evoked neural activity that emerges at the fundamental frequency. We analyzed EEG recordings obtained when subjects listened to a story read by a single speaker. We identified a response tracking the speaker's fundamental frequency that occurred at a delay of 11 ms, while another response elicited by the high-frequency modulation of the envelope of higher harmonics exhibited a larger magnitude and longer latency of about 18 ms with an additional significant component at around 40 ms. Notably, while the earlier components of the response likely originate from the subcortical structures, the latter presumably involves contributions from cortical regions. Subsequently, we determined the magnitude of these early neural responses for each individual word in the story. We then quantified the context-independent frequency of each word and used a language model to compute context-dependent word surprisal and precision. The word surprisal represented how predictable a word is, given the previous context, and the word precision reflected the confidence about predicting the next word from the past context. We found that the word-level neural responses at the fundamental frequency were predominantly influenced by the acoustic features: the average fundamental frequency and its variability. Amongst the linguistic features, only context-independent word frequency showed a weak but significant modulation of the neural response to the high-frequency envelope modulation. Our results show that the early neural response at the fundamental frequency is already influenced by acoustic as well as linguistic information, suggesting top-down modulation of this neural response.
CRIS-Team Scopus Importer:2022-08-19
Keywords: auditory brainstem; EEG; fundamental frequency; language; spoken language processing

The physics of hearing: Fluid mechanics and the active process of the inner ear - Reichenbach, Tobias; Hudspeth, A. J. (Reports on Progress in Physics, 2014)
Most sounds of interest consist of complex, time-dependent admixtures of tones of diverse frequencies and variable amplitudes. To detect and process these signals, the ear employs a highly nonlinear, adaptive, real-time spectral analyzer: the cochlea. Sound excites vibration of the eardrum and the three miniscule bones of the middle ear, the last of which acts as a piston to initiate oscillatory pressure changes within the liquid-filled chambers of the cochlea. The basilar membrane, an elastic band spiraling along the cochlea between two of these chambers, responds to these pressures by conducting a largely independent traveling wave for each frequency component of the input. Because the basilar membrane is graded in mass and stiffness along its length, however, each traveling wave grows in magnitude and decreases in wavelength until it peaks at a specific, frequency-dependent position: low frequencies propagate to the cochlear apex, whereas high frequencies culminate at the base. The oscillations of the basilar membrane deflect hair bundles, the mechanically sensitive organelles of the ear's sensory receptors, the hair cells. As mechanically sensitive ion channels open and close, each hair cell responds with an electrical signal that is chemically transmitted to an afferent nerve fiber and thence into the brain. In addition to transducing mechanical inputs, hair cells amplify them by two means. Channel gating endows a hair bundle with negative stiffness, an instability that interacts with the motor protein myosin-1c to produce a mechanical amplifier and oscillator. Acting through the piezoelectric membrane protein prestin, electrical responses also cause outer hair cells to elongate and shorten, thus pumping energy into the basilar membrane's movements. The two forms of motility constitute an active process that amplifies mechanical inputs, sharpens frequency discrimination, and confers a compressive nonlinearity on responsiveness. These features arise because the active process operates near a Hopf bifurcation, the generic properties of which explain several key features of hearing. Moreover, when the gain of the active process rises sufficiently in ultraquiet circumstances, the system traverses the bifurcation and even a normal ear actually emits sound. The remarkable properties of hearing thus stem from the propagation of traveling waves on a nonlinear and excitable medium. © 2014 IOP Publishing Ltd.
CRIS-Team Scopus Importer:2021-02-25
Keywords: basilar membrane; cochlea; hair cell; traveling wave

The Spatial Pattern of Cochlear Amplification - Fisher, Jonathan A. N.; Nin, Fumiaki; Reichenbach, Tobias; Uthaiah, Revathy C.; Hudspeth, A. J. (Neuron, 2012)
Sensorineural hearing loss, which stems primarily from the failure of mechanosensory hair cells, changes the traveling waves that transmit acoustic signals along the cochlea. However, the connection between cochlear mechanics and the amplificatory function of hair cells remains unclear. Using an optical technique that permits the targeted inactivation of prestin, a protein of outer hair cells that generates forces on the basilar membrane, we demonstrate that these forces interact locally with cochlear traveling waves to achieve enormous mechanical amplification. By perturbing amplification in narrow segments of the basilar membrane, we further show that a cochlear traveling wave accumulates gain as it approaches its peak. Analysis of these results indicates that cochlear amplification produces negative damping that counters the viscous drag impeding traveling waves; targeted photoinactivation locally interrupts this compensation. These results reveal the locus of amplification in cochlear traveling waves and connect the characteristics of normal hearing to molecular forces.
CRIS-Team Scopus Importer:2021-02-25

The steady-state response of the cerebral cortex to the beat of music reflects both the comprehension of music and attention - Meltzer, Benjamin; Reichenbach, Chagit S.; Braiman, Chananel; Schiff, Nicholas D.; Hudspeth, A. J.; Reichenbach, Tobias (Frontiers in Human Neuroscience, 2015)
The brain’s analyses of speech and music share a range of neural resources and mechanisms. Music displays a temporal structure of complexity similar to that of speech, unfolds over comparable timescales, and elicits cognitive demands in tasks involving comprehension and attention. During speech processing, synchronized neural activity of the cerebral cortex in the delta and theta frequency bands tracks the envelope of a speech signal, and this neural activity is modulated by high-level cortical functions such as speech comprehension and attention. It remains unclear, however, whether the cortex also responds to the natural rhythmic structure of music and how the response, if present, is influenced by higher cognitive processes. Here we employ electroencephalography to show that the cortex responds to the beat of music and that this steady-state response reflects musical comprehension and attention. We show that the cortical response to the beat is weaker when subjects listen to a familiar tune than when they listen to an unfamiliar, non-sensical musical piece. Furthermore, we show that in a task of intermodal attention there is a larger neural response at the beat frequency when subjects attend to a musical stimulus than when they ignore the auditory signal and instead focus on a visual one. Our findings may be applied in clinical assessments of auditory processing and music cognition as well as in the construction of auditory brain-machine interfaces.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Auditory attention; Auditory cognition; Auditory cortex; Auditory neuroscience; Cortical oscillations; Cortical response; Music processing

Threefold way to extinction in populations of cyclically competing species - Rulands, Steffen; Reichenbach, Tobias; Frey, Erwin (Journal of Statistical Mechanics-Theory and Experiment, 2011)
Species extinction occurs regularly and unavoidably in ecological systems. The time scales for extinction can vary broadly and provide information on the ecosystem's stability. We study the spatio-temporal extinction dynamics of a paradigmatic population model where three species exhibit cyclic competition. The cyclic dynamics reflects the non-equilibrium nature of the species interactions. While previous work focuses on the coarsening process as a mechanism that drives the system to extinction, we found that unexpectedly the dynamics in going to extinction is much richer. We observed dynamics of three different types. In addition to coarsening, in the evolutionarily relevant limit of large times, oscillating traveling waves and heteroclinic orbits play a dominant role. The weights of the different processes depend on the degree of mixing and the system size. By means of analytical arguments and extensive numerical simulations we provide the full characteristics of scenarios leading to extinction in one of the most surprising models of ecology. © 2011 IOP Publishing Ltd and SISSA.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Coarsening processes (theory); Phase transitions into absorbing states (theory); Population dynamics (theory); Stochastic processes

Transcranial alternating current stimulation in the theta band but not in the delta band modulates the comprehension of naturalistic speech in noise - Keshavarzi, Mahmoud; Kegler, Mikolaj; Kadir, Shabnam; Reichenbach, Tobias (NeuroImage, 2020)
Auditory cortical activity entrains to speech rhythms and has been proposed as a mechanism for online speech processing. In particular, neural activity in the theta frequency band (4–8 ​Hz) tracks the onset of syllables which may aid the parsing of a speech stream. Similarly, cortical activity in the delta band (1–4 ​Hz) entrains to the onset of words in natural speech and has been found to encode both syntactic as well as semantic information. Such neural entrainment to speech rhythms is not merely an epiphenomenon of other neural processes, but plays a functional role in speech processing: modulating the neural entrainment through transcranial alternating current stimulation influences the speech-related neural activity and modulates the comprehension of degraded speech. However, the distinct functional contributions of the delta- and of the theta-band entrainment to the modulation of speech comprehension have not yet been investigated. Here we use transcranial alternating current stimulation with waveforms derived from the speech envelope and filtered in the delta and theta frequency bands to alter cortical entrainment in both bands separately. We find that transcranial alternating current stimulation in the theta band but not in the delta band impacts speech comprehension. Moreover, we find that transcranial alternating current stimulation with the theta-band portion of the speech envelope can improve speech-in-noise comprehension beyond sham stimulation. Our results show a distinct contribution of the theta- but not of the delta-band stimulation to the modulation of speech comprehension. In addition, our findings open up a potential avenue of enhancing the comprehension of speech in noise.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Delta and theta frequency bands; Neural entrainment; Normal hearing; Speech comprehension; Speech envelope; Speech-shaped-noise; Transcranial alternating current stimulation

Transcranial Alternating Current Stimulation With the Theta-Band Portion of the Temporally-Aligned Speech Envelope Improves Speech-in-Noise Comprehension - Keshavarzi, Mahmoud; Reichenbach, Tobias (Frontiers in Human Neuroscience, 2020)
Transcranial alternating current stimulation with the speech envelope can modulate the comprehension of speech in noise. The modulation stems from the theta- but not the delta-band portion of the speech envelope, and likely reflects the entrainment of neural activity in the theta frequency band, which may aid the parsing of the speech stream. The influence of the current stimulation on speech comprehension can vary with the time delay between the current waveform and the audio signal. While this effect has been investigated for current stimulation based on the entire speech envelope, it has not yet been measured when the current waveform follows the theta-band portion of the speech envelope. Here, we show that transcranial current stimulation with the speech envelope filtered in the theta frequency band improves speech comprehension as compared to a sham stimulus. The improvement occurs when there is no time delay between the current and the speech stimulus, as well as when the temporal delay is comparatively short, 90 ms. In contrast, longer delays, as well as negative delays, do not impact speech-in-noise comprehension. Moreover, we find that the improvement of speech comprehension at no or small delays of the current stimulation is consistent across participants. Our findings suggest that cortical entrainment to speech is most influenced through current stimulation that follows the speech envelope with at most a small delay. They also open a path to enhancing the perception of speech in noise, an issue that is particularly important for people with hearing impairment.
CRIS-Team Scopus Importer:2021-02-25
Keywords: neural entrainment; normal hearing; speech comprehension; speech envelope; speech-shaped-noise; theta frequency band; transcranial current stimulation

Transient Noise Reduction Using a Deep Recurrent Neural Network: Effects on Subjective Speech Intelligibility and Listening Comfort - Keshavarzi, Mahmoud; Reichenbach, Tobias; Moore, Brian C. J. (Trends in Hearing, 2021)
A deep recurrent neural network (RNN) for reducing transient sounds was developed and its effects on subjective speech intelligibility and listening comfort were investigated. The RNN was trained using sentences spoken with different accents and corrupted by transient sounds, using the clean speech as the target. It was tested using sentences spoken by unseen talkers and corrupted by unseen transient sounds. A paired-comparison procedure was used to compare all possible combinations of three conditions for subjective speech intelligibility and listening comfort for two relative levels of the transients. The conditions were: no processing (NP); processing using the RNN; and processing using a multi-channel transient reduction method (MCTR). Ten participants with normal hearing and ten with mild-to-moderate hearing loss participated. For the latter, frequency-dependent linear amplification was applied to all stimuli to compensate for individual audibility losses. For the normal-hearing participants, processing using the RNN was significantly preferred over that for NP for subjective intelligibility and comfort, processing using the RNN was significantly preferred over that for MCTR for subjective intelligibility, and processing using the MCTR was significantly preferred over that for NP for comfort for the higher transient level only. For the hearing-impaired participants, processing using the RNN was significantly preferred over that for NP for both subjective intelligibility and comfort, processing using the RNN was significantly preferred over that for MCTR for comfort, and processing using the MCTR was significantly preferred over that for NP for comfort.
CRIS-Team WoS Importer:2021-10-15

Unidirectional amplification as a mechanism for low-frequency hearing in mammals - Reichenbach, Tobias; Hudspeth, A. J. (AIP Conference Proceedings, 2011)
Sound detection is achieved in the inner ear, or cochlea, which spatially separates frequencies. The highest frequencies are detected at the organ's base and successively lower frequencies at progressively more apical positions. Although a mechanism termed critical-layer absorption accounts for the spatial separation of frequencies above 1 kHz, hearing at lower frequencies appears to operate by a distinct mechanism that is poorly understood. We discuss a recently proposed ratchet mechanism for spatial separation of these low frequencies. This mechanism involves the synergistic interplay of two known active processes in the mechanoreceptive hair cells - active hair-bundle motility and membrane-based electromotility - to implement unidirectional amplification. It thus represents a mechanical analogue of the operational amplifier in electrical engineering. The mechanism provides a general design principle for unidirectional mechanical amplification that we have also employed to construct an active microphone. © 2011 American Institute of Physics.
CRIS-Team Scopus Importer:2021-02-25
Keywords: cochlear mechanics; electromotility; hair-bundle motility

Unidirectional mechanical amplification as a design principle for an active microphone - Reichenbach, Tobias; Hudspeth, A. J. (Physical Review Letters, 2011)
Amplification underlies the operation of many biological and engineering systems. Simple electrical, optical, and mechanical amplifiers are reciprocal: the backward coupling of the output to the input equals the forward coupling of the input to the output. Unidirectional amplifiers that occur often in electrical and optical systems are special nonreciprocal devices in which the output does not couple back to the input even though the forward coupling persists. Here we propose a scheme for unidirectional mechanical amplification that we utilize to construct an active microphone. We show that amplification improves the microphone's threshold for detecting weak signals and that unidirectionality prevents distortion. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2021-02-25

Waves on Reissner's Membrane: A Mechanism for the Propagation of Otoacoustic Emissions from the Cochlea - Reichenbach, Tobias; Stefanovic, Aleksandra; Nin, Fumiaki; Hudspeth, A. J. (Cell Reports, 2012)
Sound is detected and converted into electrical signals within the ear. The cochlea not only acts as a passive detector of sound, however, but can also produce tones itself. These otoacoustic emissions are a striking manifestation of the cochlea@s mechanical active process. A controversy remains of how these mechanical signals propagate back to the middle ear, from which they are emitted as sound. Here, we combine theoretical and experimental studies to show that mechanical signals can be transmitted by waves on Reissner@s membrane, an elastic structure within the cochlea. We develop a theory for wave propagation on Reissner@s membrane and its role in otoacoustic emissions. Employing a scanning laser interferometer, we measure traveling waves on Reissner@s membrane in the gerbil, guinea pig, and chinchilla. The results are in accord with the theory and thus support a role for Reissner@s membrane in otoacoustic emissions.
CRIS-Team Scopus Importer:2021-02-25

Zero-one survival behavior of cyclically competing species - Berr, Maximilian; Reichenbach, Tobias; Schottenloher, Martin; Frey, Erwin (Physical Review Letters, 2009)
The coexistence of competing species is, due to unavoidable fluctuations, always transient. In this Letter, we investigate the ultimate survival probabilities characterizing different species in cyclic competition. We show that they often obey a surprisingly simple, though nontrivial behavior. Within a model where coexistence is neutrally stable, we demonstrate a robust zero-one law: When the interactions between the three species are (generically) asymmetric, the "weakest" species survives at a probability that tends to one for large population sizes, while the other two are guaranteed to extinction. We rationalize our findings from stochastic simulations by an analytic approach. © 2009 The American Physical Society.
CRIS-Team Scopus Importer:2021-02-25